Engineering : how the six simple machines support the world - Mooney, Carla, 1970- (Inquire and investigate., 2025)
"How do we build skyscrapers? How did ancient people build pyramids? Why are gears an essential part of motors? In Engineering: How the Six Simple Machines Support the World, young engineers learn how mechanical, structural, civil, and other types of engineering are based on the six simple machines that humans have been using for thousands of years. The inclined plane, lever, pulley, screw, wedge,and wheel and axle are used to build roads, skyscrapers, bridges, engines, and even other tools. They are the building blocks on which more complicated machines are based. Without these six simple machines, the world would look far different and be much more work to navigate! Dive deep into the history of simple machines, from ancient times to present day, and learn the math behind how they increase efficiency and productivity through mechanical advantage. Hands-on STEM activities encourage use of the engineering design process as kids brainstorm and build practical prototypes and explore how we might employ simple machines in the future."--Back cover.